2004
DOI: 10.1159/000081373
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Isolated Foramen ovale Obstruction

Abstract: Premature obstruction of the foramen ovale is a rare but serious clinical entity. Obstruction can be associated with right ventricular failure, fetal hydrops, tricuspid regurgitation, left heart obstructive defects and supraventricular tachycardia. In most cases, the diagnosis is made at the postmortem examination. The etiology is unknown. We discuss 2 prenatal cases with the sole diagnosis of ventricular asymmetry. The right ventricle was dilated and hypertrophic, and the foramen ovale ballooned into the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…One might speculate that an isolated occlusion of the FO without additional restrictive lesions would affect mostly the development of left heart structures as a result of poor LA and LV filling, whereas additional restriction on either the RV outflow or the ductal level might favor a phenotype of RV dilation, tricuspid regurgitation and hydrops fetalis [20][21][22] . Nowlen et al proposes that early (primary) closure of the FO, due to abnormal development of the atrial septum, results in LV hypoplasia 9 and that late FO closure is more of a secondary event to aortic stenosis and LV dilation.…”
Section: Discussionmentioning
confidence: 99%
“…One might speculate that an isolated occlusion of the FO without additional restrictive lesions would affect mostly the development of left heart structures as a result of poor LA and LV filling, whereas additional restriction on either the RV outflow or the ductal level might favor a phenotype of RV dilation, tricuspid regurgitation and hydrops fetalis [20][21][22] . Nowlen et al proposes that early (primary) closure of the FO, due to abnormal development of the atrial septum, results in LV hypoplasia 9 and that late FO closure is more of a secondary event to aortic stenosis and LV dilation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the DP decreases at 35–40 gestational weeks, which may be related to the gradual closure of the FO in the late stage of pregnancy. A number of scholars have noted that fetal hemodynamics may be altered when the FO size is smaller than normal (8–16). In the current study, we observed the FO of DGWs in detail, by dividing the 958 cases into different groups, which provided referred evidence for certain fetuses accompanied with congenital heart growth restriction or early closure of the FO.…”
Section: Discussionmentioning
confidence: 99%
“…The flap of FO is usually redundant or fixed bulging in the left atrium, also called atrial septal aneurysm (ASA). Several cases of restrictive FO or ASA have been prenatally diagnosed [ 2 , 3 , 4 , 5 , 6 ]. It is frequently described as an uncommon finding, although in one large study a prevalence of 7.6% was reported [ 7 ].…”
Section: Introductionmentioning
confidence: 99%